BASLAWÍSH KLASSLARDA MUZÍKA PÁNIN OQÍTÍWDA INTERAKTIV METODLARDAN PAYDALAÍW - Tajetdinova, S.M.; Axetova, G.J. (SCIENCE and SOCIETY, 2022)
This article comprises data about the «dictation» method used in teaching music in primary school. The study of dynamic symbols focuses on the rules of application of textual, numerical and alphabetic dictation methods.
Keywords: music; dictation; dynamic symbols; forte; piano; mezzo piano; mezzo forte; pianissimo; fortissimo; diminuendo; crescendo